2019
DOI: 10.4103/apc.apc_146_17
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pediatric cardiac surgery and predictors of major complication in a developing country

Abstract: Background:Evaluating outcome and identifying predictors of major complications among children undergoing cardiac surgery are essential to improve care. We evaluated short-term outcomes of postcardiac surgery and predictors of major complications in a national referral hospital in Indonesia.Methods:A prospective cohort study was conducted from April 2014 to March 2015 on all children undergoing cardiac surgery. Participants were followed up from the time of surgery until hospital discharge and 30-day mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 24 publications
(28 reference statements)
5
32
1
2
Order By: Relevance
“…In this issue of Annals, Murni et al . present an article titled, “Outcomes of pediatric cardiac surgery and predictors of major complications in a developing country.”[1] The study analyzes the outcomes of pediatric cardiac surgeries performed at the Dr. Cipto Mangunkusumo Hospital in Jakarta, Indonesia, over a period of 1 year. They report a 13.6% 30-day mortality and a 19% incidence of major complications in a cohort of patients that were predominantly (95%) in RACHS Category 1 or 2.…”
mentioning
confidence: 99%
“…In this issue of Annals, Murni et al . present an article titled, “Outcomes of pediatric cardiac surgery and predictors of major complications in a developing country.”[1] The study analyzes the outcomes of pediatric cardiac surgeries performed at the Dr. Cipto Mangunkusumo Hospital in Jakarta, Indonesia, over a period of 1 year. They report a 13.6% 30-day mortality and a 19% incidence of major complications in a cohort of patients that were predominantly (95%) in RACHS Category 1 or 2.…”
mentioning
confidence: 99%
“…In another study from a private tertiary care institute in Pakistan, the mortality rate reported in pediatric cardiac surgeries was 6-8.7% [13]. Studies from other low- and middle-income countries have also reported higher mortality among children after cardiac surgery: Indonesia - 12.8% [14]; Iran - 12.4% [15]; Guatemala - 10.7% [16]; and India - 11.5% [17]. Contrary to this, high-income countries have reported less than 5% mortality after pediatric cardiac surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…A greater number of categories in the RACHS-1 represents progressively more difficult surgical cases. RACHS-1 classification uses surgical procedures to predict the risk associated with the operation and the measure has been used in the context of developing countries [26][27][28]. Two cardiac surgeons independently coded the procedures using the RACHS-1 classification and agreed on the final assignment.…”
Section: Data Collection and Measuresmentioning
confidence: 99%